FseI, a new type II restriction endonuclease that recognizes the octanucleotide sequence 5' GGCCGGCC 3'. - Nelson, J M (1990)
A Type II restriction endonuclease, designated FseI, has been partially purified from a Frankia species (NRRL 18528). This enzyme cleaves Adenovirus 2 DNA at three sites, but does not cleave the DNAs from bacteriophages lambda, T7, and phi X174, the animal virus SV40, pUC18 and pBR322. FseI recognizes the octanucleotide sequence 5' GGCCGG decreases CC 3' and cleaves as indicated by the arrow. The frequency of occurrence of FseI sites within sequenced regions of the human genome is similar to that for NotI sites.